Efektivitas Permainan Tradisional Balogo terhadap Kebugaran Jasmani Siswa Kelas Atas di SD Negeri 15 Buntok - irmayana; Fatkurahman Arjuna (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
ABSTRACT This study aims to analyze the effectiveness of the traditional balogo game on the physical fitness level of upper grade students of SD Negeri 15 Buntok. The methodology applied in this study is a quantitative approach with an experimental design. The instrument in this study used the TKJI test (Indonesian Physical Fitness Test) including sprinting for boys and girls aged 10 to 12 years, body lifting (Pull Up) for boys and girls aged 10 to 12 years, sitting down (Sit Up) for boys and girls aged 10 to 12 years, Vertical Jump for boys and girls aged 10 to 12 years, Medium Distance Running for boys and girls aged 10 to 12 years. Data were collected through observation and measurement of the physical fitness level of upper grade students of SD Negeri 15 Buntok before and after undergoing treatment in the form of traditional balogo games for 16 meetings. Students who participated in this study were all upper grade 4-6 elementary school students totaling 30 students, consisting of 18 boys and 12 girls. The results of the study on the subjects of 18 male students whose fitness was measured, the posttest results explained that most male students were in the less category as many as 9 students (50%). The least category was Good as many as 3 male students (16.7%) and the others were in the moderate category as many as 6 people (33.3%). And of the 12 female students whose fitness was measured, the posttest results explained that most female students were in the moderate category as many as 6 students (50%), the least category was Less as many as 2 female students (16.7%) and the others were in the good category as many as 4 people (33.3%). Of the total 30 upper grade students whose fitness was measured, the results of the upper grade students' fitness posttest explained that most students were in the moderate category as many as 12 students (40%) and in the Less category as many as 11 students (36.7%). The least in the good category were 7 students (23.3%). Keywords: Effectiveness, balogo traditional game, physical fitness, students of SD Negeri 15 Buntok.